PERFIL DE RESISTÊNCIA BACTERIANA AOS CARBAPENÊMICOS NAS CLÍNICAS DE UM HOSPITAL UNIVERSITÁRIO - Oliveira, Layse Maria Soares de; Santos, Eliege Maria dos; Costa, Yann Gonçalves Fernandes da; Oliveira, Thiago de Lima; Rodrigues, Mônica Meira Leite (Gep News, 2017)
Tipo de Apresentação: Pôster